Meaning, classification, epistemological foundation and significance of worldview - Sulaiman, Kabuye Uthman (Scholars Academic and Scientific Society (SAS), India, 2018)
The central focus of this work is on the importance of worldview, that is, why a worldview is needed and why it is important to be understood. There are several reasons why a person should understand worldview. The main argument in this paper is that, to explain people‘s knowledge, deeds, perceptions and beliefs about the existence and nature of God (theology), the ultimate nature of reality (metaphysics), the origins and nature of the universe, life, and especially Man (cosmology), the meaning and purpose of the universe, its inanimate elements, and its inhabitants (teleology), the nature and purpose of Man in general and, oneself in particular (anthropology), and the nature of value, what is good and bad, what is right and wrong (axiology), one must get to the root cause, which is the worldview. That is, the framework from which one sees and interprets reality.